Commentary on "Hydroxychloroquine and azithromycin as a treatment of COVID-19: results of an open label non-randomized clinical trial" by Gautret et al. Issue 1 (1st January 2020) - Toumi, Mondher; Aballea, Samuel
ABSTRACT: The results of a clinical trial comparing hydroxychloroquine with or without azithromycin to the standard of care for the treatment of COVID-19 were recently published by Philippe Gautret et al. This study provides outstanding results for the combination of hydroxychloroquine and azithromycin over the standard of care, but the evidence was deemed insufficiently robust to warrant a public health decision to widen the use of hydroxychloroquine for the treatment of COVID-19. We provide a scientific critical review of the Gautret et al. publication, put the results in the context of the current knowledge, provide an evaluation of the validity of the results (from a methodologic perspective), and discuss public health implications. The study has a number of limitations, including small sample size, lack of comparability between patients in active treatment and control arms, lack of blinding, use of interim analyses without controlling for the risk of type 1 error, use of analysis in the per-protocol population instead of the intention-to-treat population, and inconsistencies between the study protocol and article. However, none of these observations is of a nature to reverse the conclusions. The study brings useful knowledge consistent with available evidence and clinical practice from China and South Korea, which could have prompted quicker policy decision-making.